MSH3 promotes back-up DNA end-joining pathways that sustain the survival of BRCA2- deficient cells - Loedin, AK (2022)
DNA repair pathways that maintain genomic stability are essential in avoiding carcinogenesis. However, inactivation of these repair pathways frequently occurs during tumorigenesis and cancer cells become dependent on alternative mechanisms for DNA repair. Cancer cells with heterozygous germline mutations in BRCA1 and BRCA2 have abrogated HR function, hence they rely on alternative DSB repair pathways known to promote genomic instability, one of which is alternative non-homologous end-joining (A- NHEJ). This pathway requires the activity of error-prone DNA polymerase θ (Polθ) to anneal sequences with microhomology and utilise them as primers for DNA synthesis. Previous studies have shown that Polθ activity is critical for the survival of BRCA2- deficient cells and A-NHEJ has also been implicated in the resistance of BRCA2-deficient tumours to chemotherapy. Hence, factors of A-NHEJ represent potential targets for the elimination of BRCA-deficient tumours. The MSH2/MSH3 heterodimer has been canonically characterised in mismatch repair (MMR) in recognising long distortions in DNA structure. Notably, yeast and hamster MSH2/MSH3 displayed MMR-independent activity in repairing DNA lesions by joining DNA breaks with microhomologies, similar to A-NHEJ. The aim of this thesis was to investigate the potential role of MSH3 in the A- NHEJ pathway in BRCA2-deficient cells. We discovered that concurrent loss of MSH3 and BRCA2 reduced cell viability, thus indicating a role for MSH3 in the survival of BRCA2-deficient cells. Subsequently, we performed epistatic experiments with MSH3 and Polθ which indicated that MSH3 likely has a role in A-NHEJ. PARP-inhibitors are known to eliminate BRCA2-deficient cells. Interestingly, we observed that MSH3 loss in BRCA2-deficient cells led to their increased sensitivity to PARP inhibitor (PARPi) treatment. Thus, we have identified novel functions of MSH3 in the survival and response to treatment of human BRCA2-deficient cells.